Gambaran Hasil Screening Diabetes Melitus pada Keluarga Anggota Prolanis Maleosan - Anggie Margaretha Kubalang; Vera D. Tombokan; Jonesius Eden Manoppo (LPPM STIKES KESETIAKAWANAN SOSIAL INDONESIA, 2025)
Diabetes Mellitus (DM) remains a major global health issue with increasing prevalence, including in Indonesia. Early detection through family-based screening plays an important role in preventing complications and improving quality of life. The Prolanis program aims to control chronic diseases such as DM through community-based preventive efforts. Objective: This study aimed to describe the results of DM screening among families of Prolanis Maleosan members. Methods: A descriptive quantitative design with a cross-sectional approach was used. The study involved 125 respondents, with data collected using questionnaires on demographic characteristics, health history, and DM screening results. Data were analyzed univariately and presented in frequency and percentage. Results: Most respondents were 15–45 years old (71.2%), female (68.0%), and had senior high school education (84.0%). A total of 90.4% were diagnosed with DM, while 96.0% had low-risk health conditions. The most common comorbidity was hypertension (10.4%), followed by coronary heart disease (4.0%). Conclusion: DM prevalence among Prolanis Maleosan families is high, yet most maintain stable health. Strengthening regular screening, family health education, and community-based preventive actions is recommended.